Indoor PM₂.₅ and CO₂ Exposure and Respiratory Symptoms Among Toddlers in Daycare Centers in Surabaya - Corie Indria Prasasti; Retno Adriyani; Khuliyah Candraning Diyanah; Namira Zulaikha Putri; Ahmad Zia Ul-Saufie; Siti Nurshahida Nazli; Galuh Mega Kurnia (Universitas Airlangga, 2026)
Introduction: The high intensity of transportation and urban activities in Surabaya causes PM2.5 and CO2 exposure to fall into the unhealthy category for vulnerable group, including toddlers. The aims of this study is to investigate the association between indoor air quality and respiratory symptoms among toddlers in daycare centers in Surabaya. Methods: The research design of this study was cross-sectional and conducted in 15 daycare centers. The sample of this study were 149 toddlers aged 0–60 months and randomly selected from a total of 278 population. Respiratory symptoms were measured using the ISAAC questionnaire who was administered to parents. PM2.5 and CO2 were measured using AiRBOXSense Low-Cost Air Quality Sensors (LAQSs). Results and Discussion: The study shows that toddlers aged 24-60 months who experienced respiratory symptoms (69.4%) were higher than toddlers aged 0–24 months who experienced respiratory symptoms (30.6%). There was no significant association between respiratory symptoms and PM2.5. Significant associations were found only between respiratory symptoms and CO2 levels in the playroom (p = 0.041). Elevated levels of PM2.5 and CO2 were also observed in several daycare centers (bedroom and playroom). Conclusion: CO2 might be the only parameters that was directly associated with respiratory symptoms in this study. However, elevated PM2.5 and CO2 levels suggest potential long-term risks. Prevention efforts, continuous monitoring, and improvement of indoor environments in daycare settings were essentials to minimize potential exposures.